Peripheral Sensory Neurons Expressing Melanopsin Respond to Light - Matynia, Anna; Nguyen, Eileen; Sun, Xiaoping; Blixt, Frank W.; Parikh, Sachin; Kessler, Jason; Pérez de Sevilla Müller, Luis; Habib, Samer; Kim, Paul; Wang, Zhe Z.; Rodriguez, Allen; Charles, Andrew; et al. (Frontiers in Neural Circuits, 2016)
The ability of light to cause pain is paradoxical. The retina detects light but is devoid of nociceptors while the trigeminal sensory ganglia (TG) contain nociceptors but not photoreceptors. Melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs) are thought to mediate light-induced pain but recent evidence raises the possibility of an alternative light responsive pathway independent of the retina and optic nerve. Here, we show that melanopsin is expressed in both human and mouse TG neurons. In mice, they represent 3% of small TG neurons that are preferentially localized in the ophthalmic branch of the trigeminal nerve and are likely nociceptive C fibers and high-threshold mechanoreceptor Aδ fibers based on a strong size-function association. These isolated neurons respond to blue light stimuli with a delayed onset and sustained firing, similar to the melanopsin-dependent intrinsic photosensitivity observed in ipRGCs. Mice with severe bilateral optic nerve crush exhibit no light-induced responses including behavioral light aversion until treated with nitroglycerin, an inducer of migraine in people and migraine-like symptoms in mice. With nitroglycerin, these same mice with optic nerve crush exhibit significant light aversion. Furthermore, this retained light aversion remains dependent on melanopsin-expressing neurons. Our results demonstrate a novel light-responsive neural function independent of the optic nerve that may originate in the peripheral nervous system to provide the first direct mechanism for an alternative light detection pathway that influences motivated behavior.